2017
DOI: 10.20396/rbi.v17i1.8650856
|View full text |Cite
|
Sign up to set email alerts
|

Econometric estimation of labor productivity in the brazilian manufacturing sector in the 2000s:

Abstract: No período 2000-2008, que cobre a análise deste trabalho, enquanto o crescimento médio do PIB real no Brasil foi de 3,7% ao ano, a produtividade do trabalho na indústria de transformação apresentou variação negativa de 1,0% ao ano. No Brasil, tem sido um “clichê” avaliar as relativamente baixas taxas de crescimento econômico no período como resultado do baixo crescimento da produtividade do trabalho nas últimas décadas. No entanto, de acordo com a lei Kaldor-Verdoorn, o recíproco também poderia ser verdade: as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…They found that in municipalities with inclusive institutions and higher human capital, productivity growth responds more strongly to demand growth. Nassif et al ( 2022 ) find results that validate the Kaldor–Verdoorn law also for the case of Brazil. Concerning panel analysis, Knell ( 2004 ) estimated a Verdoorn coefficient of 0.53 with respect to the manufacturing sectors of 12 industrial countries during the 1990s; Tridico and Pariboni ( 2018 ) estimated a Verdoorn effect of 0.36 in a panel of OECD countries.…”
Section: Empirical Literaturementioning
confidence: 73%
“…They found that in municipalities with inclusive institutions and higher human capital, productivity growth responds more strongly to demand growth. Nassif et al ( 2022 ) find results that validate the Kaldor–Verdoorn law also for the case of Brazil. Concerning panel analysis, Knell ( 2004 ) estimated a Verdoorn coefficient of 0.53 with respect to the manufacturing sectors of 12 industrial countries during the 1990s; Tridico and Pariboni ( 2018 ) estimated a Verdoorn effect of 0.36 in a panel of OECD countries.…”
Section: Empirical Literaturementioning
confidence: 73%
“…A search in the Web of Science All Databases (Web of Science, 2019) and Scopus (Scopus, 2019) databases reveals that the Kaldor law is considered in several regional analysis, however a limited number of references were found for Portugal and Spain. Around the world, the Kaldor developments have been considered, for instance, for the Sub-Saharan African countries (Ssozi & Bbaale, 2019), Italy (Davanzati, Patalano, & Traficante, 2019), Mexico (Reyes, 2019), Portugal (Martinho, 2019), Asian and Latin American countries (Di Meglio, Gallego, Maroto, & Savona, 2018), Saudi Arabia (Almosabbeh & Almoree, 2018), Brazil (Nassif, Feijo, & Araujo, 2018) and China (McCombie, Spreafico, & Xu, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%